Sensory-level electrical stimulation in children with cerebral palsy: a scoping review of current applications and outcomes - de Araujo, Céline; Gschaidmeier, Alisa; von Gunten, Miriam; Grunt, Sebastian (Frontiers in Pediatrics, 2025)
IntroductionThis scoping review aims to map the existing literature on sensory-level electrical stimulation (ES) interventions for children with cerebral palsy (CP).MethodsMEDLINE, Embase and PEDro were searched. Among 504 screened articles, 18 studies were included. ES forms utilized included transcutaneous electrical nerve stimulation (TENS), therapeutic electrical stimulation (TheES), threshold electrical stimulation (ThrES), Mesh-Glove Stimulation, and the Mollii suit. The reviewed ES modalities were used in upper extremities, lower extremities, and whole-body treatments.ResultsSome significant improvements were noted in motor control, spasticity, strength, and functional abilities.DiscussionWhile the findings suggest that sensory-level ES holds promise for enhancing motor function in children with CP with significant improvements shown in the relevant outcome measures in fourteen of eighteen papers, the existing literature is characterized by significant variability in stimulation parameters, study design, sample sizes, patient characteristics and outcome measures hindering the ability to generalize findings. Further research with larger, more homogeneous samples and standardized protocols are essential to validate these interventions and establish effective treatment guidelines.